Design of live-attenuated animal vaccines based on pseudorabies virus platform - Zhen Liu; Zhengjie Kong; Meng Chen; Yingli Shang (BMC, 2022)
Abstract Pseudorabies virus (PRV) is a double-stranded DNA virus with a genome approximating 150 kb in size. PRV contains many non-essential genes that can be replaced with genes encoding heterogenous antigens without affecting viral propagation. With the ability to induce cellular, humoral and mucosal immune responses in the host, PRV is considered to be an ideal and potential live vector for generation of animal vaccines. In this review, we summarize the advances in attenuated recombinant PRVs and design of PRV-based live vaccines as well as the challenge of vaccine application.